Hassan Melehy. Kerouac: Language, Poetics, and Territory. New York: Bloomsbury Academic, 2016. - Susan Pinette (Studies in 20th & 21st Century Literature, 2017)
Review of Hassan Melehy. Kerouac: Language, Poetics, and Territory. New York: Bloomsbury Academic, 2016.
Keywords: Book Review; French Canadians; Franco Americans; Kerouac